Association and mediating mechanism between remnant cholesterol and first-ever stroke among the Chinese general population - Li, Heng; Miao, Shuai; Chen, Lu; Liu, Bin; Li, Yan-Bin; Duan, Rui-Sheng (Frontiers in Neuroscience, 2023)
Background Remnant cholesterol (RC) has been suggested to be implicated in atherosclerosis. The objective of the study was to evaluate the association between RC and first-ever stroke in the Chinese general population and to investigate whether the association is mediated via hypertension or diabetes. Methods This study is a retrospective cohort analysis of participants from the China Health and Nutrition Survey. Participants without previous stroke and myocardial infarction in 2009 were enrolled and followed up in 2011 and 2015. Logistic regression analyses were adopted to explore the association of RC with stroke risk. Propensity score methods and doubly robust estimation method were used to ensure the robustness of our findings. Potential mediators were identified by mediation analyses. Results A total of 7,035 participants were involved, and during 6 years of follow-up, 78 (1.1%) participants experienced a first-ever stroke. Participants with high RC had a significantly higher incidence of stroke (1.4% versus 0.8%; p = 0.007). High RC was associated with 74% higher stroke risk after adjusting for multiple relevant variables (odds ratio [OR], 1.74; 95% CI, 1.06–2.85). The association was consistent in analyses using propensity score methods and doubly robust estimation method. Hypertension showed a significant mediating effect on the association between RC and stroke, while the mediating effect of diabetes was not significant. Conclusion High RC increased the risk of first-ever stroke in the Chinese general population without previous stroke and myocardial infarction, partially through the pathway of hypertension. RC might be a potential target for the primary prevention of stroke.